Integration of AHP and Modified VIKOR Method to Select the Optimum Destination Route - Simbolon, Miranda Melania Nathasia; Gultom, Parapat; Rosmaini, Elly (Sinkron : jurnal dan penelitian teknik informatika, 2024)
One common approach to rating options is group decision making using many criteria. Here, we use the same criteria to evaluate each option. Sometimes, decision makers are faced with some situations where they have to choose from a set of alternatives that have several different criteria. Thus, the decision maker cannot use a common method. Therefore, in this research, a modification to a method is carried out. To address the issue of developing alternate routes to Medan City's historical tourism attractions, the AHP and VIKOR approaches have been suggested. When considering options with both specific and broad requirements, this study adapts the VIKOR technique to find a workable solution. In order to demonstrate the suggested model's use and evaluate the efficacy of this approach change, this study offers numerical examples based on case studies. The findings demonstrate that the revised approach is both practical and efficient.